SDRP: secure and dynamic routing protocol for mobile ad‐hoc networks. Issue 3 (1st September 2014) - Ghosh, Uttam; Datta, Raja
Abstract : RSA‐based secure routing protocols are computationally expensive because of the use of large public keys and/or signatures that are disadvantageous for mobile ad‐hoc networks. In this study, the authors proposed a secure dynamic routing protocol, named SDRP, which uses identity‐based scheme with pairing on elliptic curve. It makes use of signature and 'Message Authentication Code' algorithms to provide end‐to‐end, hop‐to‐hop and whole‐route authentications. The proposed SDRP has several advantages over the existing RSA‐based secure routing solutions. Firstly, it requires fewer signature generations and verifications on a route. Secondly, the SDRP makes use of an identity‐based scheme which is certificate‐less, thus saving routing overhead (RO) and storage. Finally, it uses a hardware address to generate its small size of public key. Both the qualitative analysis and the simulation results show that the proposed SDRP provides secure routes and better packet delivery fraction and with significantly less RO and latency compared with previous RSA‐based secure routing protocols.